Contrasting Behaviors of 210Pb and 210Po in the Productive Shelf Water Versus the Oligotrophic Water - Seo, Hojong; Joung, DongJoo; Kim, Guebuem (Frontiers in Marine Science, 2021)
We measured the total, truly dissolved (< 10 kDa), colloidal (10 kDa–0.2 μm), and particulate phases (> 0.2 μm) of 210Pb and 210Po in the East China Sea (ECS) shelf water and the East Sea (Japan Sea). In order to examine the behaviors of 210Pb and 210Po in different marine environments, we compiled our results with previously reported data in the same region and in the northwestern Pacific Ocean (NWPO). The proportions of the truly dissolved, colloidal, and particulate phases in the shelf water were 32%, 27%, and 41% for 210Pb and 49%, 32%, and 19% for 210Po, respectively. Based on a steady-state scavenging model, 210Pb and 210Po showed higher scavenging rate (3.0 ± 0.6 y-1) and lower scavenging rate (0.3 ± 0.2 y-1), respectively, in the shelf water than those in the NWPO and the East Sea. A non-steady-state model, accounting for the residence time of the shelf water, also showed the twice more efficient removal rate of 210Pb in the shelf water than that in the NWPO and the East Sea. In contrast, there was the net input of 210Po in the shelf water relative to the large removal in the NWPO and the East Sea, which was opposite to the 210Pb trend. The large proportions of total dissolved (truly dissolved + colloidal) 210Po (> 80%) in the shelf water indicate active regeneration of 210Po from the sinking particles and the surface sediments. Our results suggest that the ECS shelf is the source for Po in the northwestern Pacific marginal seas, a proxy for sulfur group elements (S, Se, and Te), whereas it is the efficient sink for Pb, together with other particle-reactive trace elements.